Analisis Penerapan Program GMP dan 5P Terhadap Kinerja Karyawan di PT Kalbe Morinaga Indonesia - Halily Sofyan Al Hasan; Muhammad Ali Akbar; Ade Elza Surachman (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study aim is to know the effect of the implementation of Good Manufacturing Practices Program, 5P Program related on Employee Performance at PT. Kalbe Morinaga Indonesia. This research is located in PT. Kalbe Morinaga Indonesia with 390 people population and the sample taken is 84 people using stratified random sampling technique with Slovin formula which is conducted from May to June 2018. Approachment to data analyze using Partial Least Square (PLS), namely Smart-PLS 3.0. Based on the analysis results obtained that Good Manufacturing Practices Program has a positive effect on Employee Performance and 5P Program also has a positive effect on Employee Performance.